Optimization of flow forming process parameters of al-8014 using genetic algorithm - Mahender, T; Venkatesh, Bellam (International Journal of Engineering and Technology, 2018)
Flow forming is an advanced version of the metal spinning process in which the metal is formed into the desired shape without formation of a chip. There are many flow forming process parameters that will influence the surface roughness of the material. In the current study, three process parameters are considered in the flow forming of AA8014. The process parameters are speed of the mandrel, longitudinal feed and the flow rate of the coolant and the response is surface roughness. Design of experiments based response surface method (RSM) is used to study the effect of process parameters on the response. A quadratic mathematical model was developed by RSM is used for optimization of surface roughness by using an evolutionary technique Genetic Algorithm. The surface roughness obtained at optimum process parameters from Genetic Algorithm is in good agreement with the experimental results. Â Â